Finite groups with a prescribed number of cyclic subgroups. Issue 3 (4th March 2019) - Belshoff, Richard; Dillstrom, Joe; Reid, Les
Abstract: Marius Tărnăuceanu described the finite groups G having| G | − 1 cyclic subgroups. We describe the finite groups G having| G | − Δ cyclic subgroups forΔ = 2, 3, 4, and 5.